Pelatihan Pengembangan Modul Ajar Berbasis TPACK pada Kurikulum Merdeka di SDN Madyopuro 01 Kota Malang - Radeni Sukma Indra Dewi; Shirly Rizki Kusumaningrum; Riska Pristiani; Ade Eka Anggraini; Lia Nur Atiqoh Bella Dina; Safitri Wulandari; Ma'ruf Mustofa; Mochamad Auliya' Akbar (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The training on developing TPACK-based (Technological Pedagogical Content Knowledge) teaching modules at SDN Madyopuro 01, Malang City, aims to enhance teachers' competencies in integrating technology into teaching in line with the Merdeka Curriculum. This initiative is motivated by the need to modernize teaching methods and increase student engagement through technology. Teachers were trained to create relevant and innovative teaching modules through a series of training activities, including the introduction of the TPACK concept, technical training on using technology, and workshops on teaching module development. The results of this training show a significant improvement in teachers' understanding and skills, with 85% of participants able to develop TPACK-based teaching modules independently. The outcomes of this activity include 12 ready-to-use TPACK-based teaching modules, as well as increased teacher motivation and engagement in the teaching process. This training successfully supports the implementation of the Merdeka Curriculum at the school, creating a more adaptive and responsive learning environment to meet the needs of the times.